VALIDASI SYARAT TASALSUL DAN NISBAH PERAWI: Studi Hadis Kawasan Hadis Musalsal Bi Mishriyin yang Diriwayatkan Oleh Jalaluddin As-Suyuthi dalam Jiyad Al-Musalsalat - Angger Wisnuaji (DIRAYAH : Jurnal Ilmu Hadis, 2024)
This study discusses the validity of the tasalsul requirements of the musalsal bi al-Mishriyin hadith narrated by Jalaluddin Abdur Rahman as-Suyuthi in his book Jiyad al-Musalsalat, in the science of hadith, there is one type of hadith that is famous for its weaknesses, because it was narrated to our day. this, namely the musalsal hadith that requires special procedures or characteristics in its transmission, because of its uniqueness in this transmission, many major hadith scholars also participate in narrating it even though most of this type of hadith is weak, therefore in order to distinguish whether it is authentic or dhaif especially for people lay. This study uses a literature study by analyzing and matching the content of the biographical books of narrators or Mu'jam Buldan and the names of the narrators written by as-Suyuthi in his book Jiyad al-Musalsalat. he must have a ratio to the Egyptian state. Based on the results of the analysis, it can be seen that all the narrators mentioned by as-Suyuthi in his sanad have a ratio to the Egyptian state, but there are some narrators who are not originally Egyptian but have lived in Egypt for a long period of time.